If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6-6x=9
We move all terms to the left:
-6-6x-(9)=0
We add all the numbers together, and all the variables
-6x-15=0
We move all terms containing x to the left, all other terms to the right
-6x=15
x=15/-6
x=-2+1/2
| -4x(x+3)=18 | | n/4+7=-2 | | d/6+12=7 | | 4(w-6)=3(w+1 | | 3y−16=2y+2 | | 5m-13=8 | | 5(2x–1)=8x+1 | | 3x-21=6x-39 | | 4x-33=57+7x | | -4(x+3)=18 | | -5x-1=24 | | x2-4=45 | | 7=4+3u | | 114=1/3x-3 | | 5y+6=111 | | —18+5x=-12x-1 | | (x+4)+((x+9)+4)=91 | | 10/20=1x | | 1/2x0.75=5.75 | | 4x+33=57+7x | | 110=5a-10 | | 1/2x+3/4=2x-8 | | (6x+175)=(3x+127) | | -4(x+3=18 | | 5(8-7b)=-100 | | 11+2x=31+7x | | (n-5)/6+(n+3)/7=(11/21) | | 4z-8=4z-8 | | 7x+3x-7=63 | | 3(5x+7)=8(x+2) | | 4x=1/2x+15 | | 2x+19+4x=49 |